2019
DOI: 10.21203/rs.2.19354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Midwives' Perspectives of Respectful Maternity Care during Childbirth: A Qualitative Study

Abstract: Background: The adoption of respectful maternity care during labour and birth is complex process which needs both scientific and interpersonal skills of providers. In this regard, identifying the potential barriers and applying effective strategies for implementing respectful maternity care are essential. This study aimed to explore the perceptions of Iranian midwives regarding respectful maternity care during labour and childbirth.Methods: This was a qualitative study which was conducted from September-Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This highlights that instead of being dismissive, health care providers can step in to moderate fear by listening to a couple’s requests and verbal expressions of fear by acknowledging their fear and communicating with them constantly to build trust. The latest study reported that women were less afraid when they had more confidence in their obstetricians and midwives (Moridi et al, 2020), further reinforcing the need of receiving compassionate and dignified care from health care providers. A recent study also discussed that keeping fathers informed of the events during childbirth and constantly keeping them involved in providing support for their partners helped them to cope with negative outcomes of childbirth better (Elmir & Schmied, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that instead of being dismissive, health care providers can step in to moderate fear by listening to a couple’s requests and verbal expressions of fear by acknowledging their fear and communicating with them constantly to build trust. The latest study reported that women were less afraid when they had more confidence in their obstetricians and midwives (Moridi et al, 2020), further reinforcing the need of receiving compassionate and dignified care from health care providers. A recent study also discussed that keeping fathers informed of the events during childbirth and constantly keeping them involved in providing support for their partners helped them to cope with negative outcomes of childbirth better (Elmir & Schmied, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reference lists of these papers were also examined. Literature review was followed by a qualitative study, the details of which are described elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Disrespectful care is associated with low satisfaction with care (Kujawski et al, 2015), psychological distance between women and health care providers (Ishola et al, 2017), and low future uptake of facility-based health care by women (Ishola et al, 2017;Kujawski et al, 2015;Ndwiga et al, 2014) which may contribute to increased maternal and neonatal mortality and morbidity. Several qualitative studies have explored midwives' and students' perspectives of disrespectful and abusive care (Burrowes et al, 2017) and midwives' perspectives of RMC (Moridi et al, 2020b;Ndwiga et al, 2017). Some authors have used study-specific questionnaires to explore midwives' perceptions of disrespectful care (Afulani et al, 2020) and nursing students' perceptions of obstetric violence (Mena-Tudela et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%